THE ENCOUNTER BETWEEN THE WEST AND ISLAM IN ECOLOGY - Muhammad, Afda Alif; Fazrian, Muhammad Ihza (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
This article seeks to discuss the encounter of Arne Naess’s theoretical ecology model and al-Qusyairi's Sufism theory, Ecosufism. To examine their relationship, this article employ Arne Naess's triangulation model of shallow ecology, deep ecology, and complexity, which in Al-Qusyairi’s sufism is referred to as tauḥīd, tazkiyyat an-nafs, and muḥsīn. Thus, this article highlights the sufi figure of akhlāqī (al-Qusyairi) as the subject of philosophical content. This article argues that to lead modern society towards a deeper understanding and practice can be accomplished with spirituality and ecology proceeding together (juxtaposition) in fostering “respectful” behavior toward all creatures. This approach benefits the environment (nature-oriented) and also enriches the individual's spirituality (God-oriented).